THE EFFECT OF PEER-ASSISTED LEARNING STRATEGYIN READING COMPREHENSION - Riki Ainul Yakin; I Made Permadi Utama; Tri Setianingsih (Sinar Lima, 2026)
This study investigates the effect of the Peer-Assisted Learning Strategy on students’ reading comprehension at MA Manba'ul Ulum Kabul in the academic year 2025/2026. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The sample consisted of 30 eleventh-grade students divided into an experimental group and a control group. The experimental group was taught using the Peer-Assisted Learning Strategy, while the control group was taught using a guided reading strategy. The data were collected through pre-test and post-test instruments consisting of 25 multiple-choice questions. The data were analyzed using descriptive statistics, normality test, homogeneity test, and independent samples t-test. The results showed that the post-test mean score of the experimental group (76.9) was higher than that of the control group (72.3). The independent samples t-test revealed a significant difference between the two groups (t = 3.420, p = 0.002 < 0.05). Therefore, it can be concluded that Peer-Assisted Learning Strategy has a significant positive effect on students’ reading comprehension.